La bucanera de Pernambuco o Hilda la polígrafa:experimentación formal, abyección grotesca y humor en Alejandra Pizarnik - María José Bruña Bragado (Cuadernos LIRICO)
This article explores the text titled La bucanera de Pernambuco o Hilda la polígrafa, one of the latest written by the Argentinean writer Alejandra Pizarnik. Through the theorical notions of baroque, grotesque and abyection, this work tries to analyze these bizarre and different proses in the context of the work of this author. La bucanera de Pernambuco o Hilda la polígrafa make obvious a life instinct.